The importance of genotyping within the climate-smart plant breeding value chain – integrative tools for genetic enhancement programs - Garcia-Oliveira, Ana Luísa; Ortiz, Rodomiro; Sarsu, Fatma; Rasmussen, Søren K.; Agre, Paterne; Asfaw, Asrat; Kante, Moctar; Chander, Subhash (Frontiers in Plant Science, 2025)
The challenges faced by today’s agronomists, plant breeders, and their managers encompass adapting sustainably to climate variability while working with limited budgets. Besides, managers are dealing with a multitude of issues with different organizations working on similar initiatives and projects, leading to a lack of a sustainable impact on smallholder farmers. To transform the current food systems as a more sustainable and resilient model efficient solutions are needed to deliver and convey results. Challenges such as logistics, labour, infrastructure, and equity, must be addressed alongside adapting to increasingly unstable climate conditions which affect the life cycle of transboundary pathogens and pests. In this context, transforming food systems go far beyond just farmers and plant breeders and it requires substantial contributions from industry, global finances, transportation, energy, education, and country developmental sectors including legislators. As a result, a holistic approach is essential for achieving sustainable and resilient food systems to sustain a global population anticipated to reach 9.7 billion by 2050 and 11.2 billion by 2100. As of 2021, nearly 193 million individuals were affected by food insecurity, 40 million more than in 2020. Meanwhile, the digital world is rapidly advancing with the digital economy estimated at about 20% of the global gross domestic product, suggesting that digital technologies are increasingly accessible even in areas affected by food insecurity. Leveraging these technologies can facilitate the development of climate-smart cultivars that adapt effectively to climate variation, meet consumer preferences, and address human and livestock nutritional needs. Most economically important traits in crops are controlled by multiple loci often with recessive alleles. Considering particularly Africa, this continent has several agro-climatic zones, hence crops need to be adapted to these. Therefore, targeting specific loci using modern tools offers a precise and efficient approach. This review article aims to address how these new technologies can provide a better support to smallholder farmers.